Differentiated Instructions in Teaching English for Students with Autism Spectrum Disorder - Sandra, Lifia Alex; Kurniawati, Lemmuela Alvita (Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to explore the gacor5000 use of differentiated instructions in teaching English for students with Autism Spectrum Disorder (ASD) and investigate English teachers’ views on the extent of differentiated instructions in teaching English for students with ASD gacor5000. The participants of this study was two English lecturers of English language education department in a private inclusive university in Indonesia. Employing qualitative method hagoslot, this study used the data gathered from the interviews with the participants. This study used thematic analysis and generated five themes regarding to the wede168 use of differentiated instructions and teachers’ views on it. The first three themes were used to explain the extent of differentiated instructions in teaching English for students with ASD. The first three themes are the participants used differentiated class-assignments for students with ASD in their English class, they used differentiated content materials for students with ASD, and lastly, they provided outside-class assistance for students with ASD. The last two themes were used to reveal teachers’ vi.ws on the extent of differentiated instructions in teaching English for students with ASD. First, differentiated instructions lessened the level of anxiety of students with ASD, and second, differentiated instructions provided a positive learning environment for students with ASD. Based on the results and limitation of the study, some implications, contributions, and suggestions for future studies are presented.